Reinforced Optical Properties of Sm3+ Complexes with β-Hydroxyketone Ligand by Using Methylated Auxiliary Ligands - Poonam; Khatri, Savita; Kumar, Manoj; Bhayana, Seema; Khatkar, S.P.; Taxak, V.B.; Kumar, Rajesh (Asian Journal of Chemistry, 2022)
Solution precipitation method was used to synthesize two avant-grade ternary complexes of Sm3+ ion with 2-hydroxy-4,6-dimethoxy-acetophenone (HDMA) as prime ligand and 5,6-dimethyl-1,10-phenathroline (dmphen) as auxillary ligand. Characterization of these complexes was accomplished by means of elemental analysis, 1H NMR, FT-IR and photoluminescence spectroscopy. Emission spectra recorded at ambient temperature, displayed sharp emission bands at 564, 600 and 646 nm attributed to 4G5/2®6Hj (j = 5/2, 7/2, 9/2) f-f transitions of metal ion. The decent decay time of luminescence and superior colour purity reported in complexes. The correlated colour temperature of these complexes established them as warm light source. The quantum yield was also evaluated for both complexes. HDMA alone could sensitize Sm3+ ion proficiently but the inclusion of auxillary ligands neocuproine (neo) or 5,6-dimethyl-1,10-phenathroline (dmphen) resulted in reinforced optical properties. The results of emission spectra illustrated that these ternary complexes can be one of the most promising substances for fabrication of display devices.